1983
DOI: 10.1128/iai.39.2.676-685.1983
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms That Control Bacterial Populations in Continuous-Flow Culture Models of Mouse Large Intestinal Flora

Abstract: A previous study had established that anaerobic continuous-flow (CF) cultures of conventional mouse cecal flora were able to maintain the in vivo ecological balance among the indigenous bacterial species tested. This paper describes experiments designed to determine the mechanisms which control the population sizes of these species in such CF cultures. One strain each of Escherichia coli, Fusobacterium sp., and Eubacterium sp. were studied. Growth of these strains in filtrates of CF cultures was considerably m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
0
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(153 citation statements)
references
References 21 publications
(20 reference statements)
4
141
0
3
Order By: Relevance
“…Further experiments should be performed to explore differences in regulation of the asp operon between the two bacterial strains. The fact that EHEC is more efficient than commensal E. coli in assimilating aspartate is consistent with the Freter's nutrient-niche theory that postulates that a microorganism can coexist in the mammal intestine by utilizing limiting nutrients better than the other bacterial species (Freter et al, 1983) and supports a key role for aspartate during EHEC multiplication in the bovine gut.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Further experiments should be performed to explore differences in regulation of the asp operon between the two bacterial strains. The fact that EHEC is more efficient than commensal E. coli in assimilating aspartate is consistent with the Freter's nutrient-niche theory that postulates that a microorganism can coexist in the mammal intestine by utilizing limiting nutrients better than the other bacterial species (Freter et al, 1983) and supports a key role for aspartate during EHEC multiplication in the bovine gut.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, it is accepted that the growth rate of a particular bacterium in the intestine is defined by its ability to occupy different ecological niches (Freter et al, 1983). If the key role of aspartate in EHEC multiplication is confirmed in the bovine intestine in vivo, an ecological strategy (e.g., the use of probiotics with a high affinity for aspartate) could be considered in future studies in order to reduce EHEC carriage before slaughter and to limit food contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence that CR could be largely directly mediated by the microbiota stems from in vitro gut fermentation models in continuous flow (CF) cultures. CF cultures can be inoculated with human or animal fecal material and, under controlled pH, temperature, and oxygen conditions, different regions of the intestinal tract can be modeled (Freter et al, 1983b;Payne et al, 2012). These systems are employed to assess the impact of probiotics, food additives, dietary components or drugs on microbiota composition or metabolism.…”
Section: Mechanisms Of Direct Microbiotamediated Crmentioning
confidence: 99%
“…by antibiotics, drugs) of the microbial ecosystem are more readily achieved in CF models than in animal models or human studies. CR is provided in anaerobic CF cultures, as demonstrated by repression of E. coli growth (Freter et al, 1983b). Further disturbance of the microbiota in CF cultures alleviates CR and leads to increased titers of S. Typhimurium, Freter et al (1983a, b) states that the populations of most indigenous intestinal bacteria are controlled by substrate competition, that is, that each species is more efficient than the rest in utilizing one or a few particular substrates and that the population level of that species is controlled by the concentration of these few limiting substrates (Freter et al, 1983a, b).…”
Section: Mechanisms Of Direct Microbiotamediated Crmentioning
confidence: 99%
“…This was reinforced by experiments eval- uated at the ultra structural level, using electron microscopy [22]. The mechanisms suggested in the protective e¡ect of probiotic microorganisms [16] are very broad: from competitive exclusion [17], nutrient competition [31], production of antagonistic substances (lactic acid, hydrogen peroxide [32], bacteriocins [33]) up to immune system stimulation [14,15]. From the results obtained in the present paper, it can be suggested that the intervention of the immune system could be involved as one of the main mechanisms responsible for the protective e¡ect exerted on S. pneumoniae infection and is based on the following grounds:…”
Section: Discussionmentioning
confidence: 99%